Increasing the stability of the power supply system under conditions of unstable load when powering the charging infrastructure of electric vehicles - Гнатова, Ганна Андріївна (Харківський національний автомобільно-дорожній університет, 2023)
Object: to engineer robust mechanisms that bolster the electricity network amid escalating demand, particularly from substantial and relatively unpredictable consumers such as electric vehicle (EV) charging stations, given the prevalent trend of at-home EV charging, which introduces considerable variability and control challenges into the system. Object: the process of load control in response to heightened electricity demands, particularly in scenarios where demand outstrips supply. Subject: the methodological approach to managing load demands when they exceed supply capabilities. In the course of the thesis, the theoretical aspects of urban electricity consumption were considered. An analysis of existing load-shedding techniques was carried out. The methodology of optimizing load shed as a protective measure for electricity networks is presented. The methodology can be utilized in the electricity networks for the improvement of their stability. The issue of labor protection and safety in emergency situationswas considered.
Keywords: load control; optimization; electric car; efficiency; blackout; unstable load; charging EV infrastructure